Radiological safety of groundwater around a uranium mine in Namibia. (June 2021) - Mathuthu, Manny; Uushona, Vera; Indongo, Vaino
Abstract: Uranium mining activities produce the main element used in nuclear energy production. However, it can also negatively affect the environment including groundwater by release of residues or effluent containing radioactive elements. The study investigated the concentration and radiological hazard of uranium in groundwater and seepage water from the tailings of a uranium mine in Namibia. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to assess the concentration of uranium in the groundwater and seepage water and the radiological hazards were determined. The radiological hazard indices Radium equivalent activity (Raeq ), Absorbed dose (D), Annual Effective Dose equivalent (AEDE), External hazard index (Hex) and Internal hazard index (Hin ) were determined and compared to limits recommended by United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). The calculated average value of D and Hin of groundwater is 108.11nGyh −1 and 1.26, respectively and are above the UNSCEAR values (55 nGyh −1 and 1). Further, the average values of Raeq, AEDE and Hex were below the recommended values. The isotopic ratio of uranium radionuclides in groundwater indicates that the uranium in the sampled groundwater is below 1 suggesting it is not natural uranium present but a possible contamination from the mine seepage. The radiological hazard parameters of the seepage water were above the recommended values and thus pose a radiation risk to human and environment.